Perspectives on Player Performance during FIFA World Cup Qatar 2022: A Brief Report - Luís Branquinho; Pedro Forte; Ronaldo V. Thomatieli-Santos; Elias de França; Daniel A. Marinho; José E. Teixeira; Ricardo Ferraz (MDPI AG, 2023)
Changing the date of the FIFA World Cup Qatar 2022 may represent a factor to consider for the expected performance of participating players. This was due to fixture congestion at the start of the season and expected weather conditions during the competition. Thus, the main purpose of this brief report was to critically analyze the potential impact of changing the competition date and weather conditions on players' performance. In addition, a brief description about the performance during the World Cup is also provided. For the research, the Web of Science, PubMed and SPORTDiscus databases were accessed using the primary keywords FIFA World Cup and World Soccer Cup associated with the secondary keywords match running performance, fixture congestion, fatigue and weather conditions. After applying inclusion and exclusion criteria, 52 articles were considered for analysis. The results seem to indicate that although changes were expected due to the modifications made (i.e., the competition date and scheduling congestion), the performance of the players seems not to have been affected in terms of the analyzed indicators. Furthermore, it seems possible to identify some patterns in the behavior of the teams that reached the most advanced stages of the competition.